ANALISIS YURIDIS PENGESAHAN PERKAWINAN BEDA AGAMA DAN AKIBAT HUKUMNYA (STUDI PENETAPAN NO. 156/PDT.P/2010/PN.SKA TENTANG PERKAWINAN BEDA AGAMA) - YUDI PRANATA (PREMISE LAW JURNAL, 2016)
A marriage is very important and sacred because it is a profound wedlock between a husband-to-be and a wife-to-be who want to establish a family and a household by committing a marriage. The problems of the research were as follows: how about the regulation on prohibiting a mixed marriage according to the Marriage Law in Indonesia, how about the legal consequence of a mixed marriage according to the Marriage Law in Indonesia, and how about the consideration of the panel of judges in the Ruling No. 156/Pdt./2010/PN.Ska on the Request for a Mixed Marriage. The research uses descriptive and judicial normative method.  The regulation on the prohibition of a mixed marriage in Indonesia is clearly regulated; but, in reality, is still ineffective because there is different perspective in interpreting the Article on the prohibition of a mixed marriage. The legal consequence of a mixed marriage is in Article 2 of Law No. 1/1974 on Marriage. The consideration of the Panel of Judges in the Ruling No. 156/Pdt./2010/PN.Ska on the Request for a Mixed Marriage places the emphasis on Article 57 of Law No 1/1974 on Marriage which regulates a Mixed Marriage. Keywords: Marriage, Prohibition of Marriage, Different Religions